Spatial network structure and driving factors of human settlements in three Northeastern provinces of China - Song, Rui; Li, Xueming; Hou, Xinyu (Frontiers in Ecology and Evolution, 2023)
The spatial network structure of urban human settlements has increasingly become an important factor affecting their health and sustainability levels. Its influencing factors play an important role in promoting the improvement of human settlements. Taking 34 prefecture-level cities in the three Northeastern provinces of China from 2005 to 2020 as the research objects, this paper applies a modified gravitational model to construct the spatial association relationship of urban human settlements. Furthermore, it introduces a social network analysis method, modularity, and QAP (quadratic assignment procedure) relationship regression model to explore the characteristics of the association network and its influencing factors. During the study period, the spatial correlation intensity of urban human settlements in the three Northeastern provinces of China was gradually strengthened. However, the average network density was 0.217675 during the study period, and the loose network relationship had little impact on individual units, indicating a lower level of network cohesion, this may imply that within the studied region, the interconnectivity among cities is not yet extensive, and there may exist certain levels of isolation or limited comprehensive interactions. The average network hierarchy at this stage was 0.178225, and the network structure needed to be optimized and adjusted, but the average network efficiency in the same period was 0.714025. This shows that the number of redundant relationships in this region is lower under known conditions. Among the individual characteristics of the spatial association network of human settlements, a polycentric network pattern with Shenyang, Dalian, Changchun, Daqing, Harbin, and other cities as the core and sub-core has gradually formed, and the urban network pattern has essentially stabilized. Based on urban human settlements spatial association networks, "small groups" and community organizations are intertwined overlap. The main principles of feature flow are geographic proximity and merit-based linkages. By breaking the boundary barriers of administrative regions, shortening the flow time and distance between elements to alleviate spatial friction and accelerate the flow of human settlements elements. Measures such as increasing the income of urban residents and increasing government investment in urban infrastructure can promote the balanced and coordinated development of networks and optimize network structure.